The research of Ukrainian Internet-environment for the marketing activity of industrial companies - I.L. Lіtovchеnкo (Marketing i Menedžment Innovacij, 2011)
The territorial differentiation of economy of Ukraine was researched with the help of the complex of indexes which represent innovative development. On its basis it was offered classification of administrative areas for the estimation of potential typification of Internet-environment with the purpose of effective activity the domestic industrial enterprises in the conditions of the informative economy.